2017
DOI: 10.5232/ricyde2017.04903
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de un entrenamiento pliométrico en extremidades superiores e inferiores en el rendimiento físico en jóvenes tenistas. [Effects of upper and lower body plyometric training on physical performance in young tennis players].

Abstract: El objetivo del presente estudio fue evaluar el efecto de un entrenamiento pliométrico (ejercicios en extremidades superiores e inferiores) en acciones físicas explosivas específicas en jóvenes tenistas. Veintiún jóvenes tenistas (11 chicos, 10 chicas; media de edad 14.33 ± 1.77 años) participaron en el presente estudio y fueron divididos de forma no aleatoria en grupo control, el cual continuó con su entrenamiento habitual de preparación física y en experimental, al que se le sustituyó su entrenamiento de pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 4 publications
(6 reference statements)
1
17
1
13
Order By: Relevance
“…Biological maturation plays a determining role in increasing skeletal muscle mass and muscle strength [15], which highlights the importance of controlling this type of anthropometric parameter with this technique, to achieve adequate monitoring of the training effects, competition, and injury prevention [12]. A greater muscular component has been related to a higher level of training and physical performance, the development of an improved stroke and fast and powerful tennis movements [35]. Furthermore, the physical demands of tennis training become greater as youth tennis players participate in more important competitions in junior or in adult tournaments, increasing both the intensity and the duration of the games, such that more muscle power is necessary [36] The findings of low explanatory percentages with respect to body fat, for chronological age and biological age in both genders are contrary to those reported in other studies, which found more significant relationships between these indicators [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…Biological maturation plays a determining role in increasing skeletal muscle mass and muscle strength [15], which highlights the importance of controlling this type of anthropometric parameter with this technique, to achieve adequate monitoring of the training effects, competition, and injury prevention [12]. A greater muscular component has been related to a higher level of training and physical performance, the development of an improved stroke and fast and powerful tennis movements [35]. Furthermore, the physical demands of tennis training become greater as youth tennis players participate in more important competitions in junior or in adult tournaments, increasing both the intensity and the duration of the games, such that more muscle power is necessary [36] The findings of low explanatory percentages with respect to body fat, for chronological age and biological age in both genders are contrary to those reported in other studies, which found more significant relationships between these indicators [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…En relación con el somatotipo, el único estudio que dio cuenta de esta variable fue el de Yáñez-Sepúlveda et al ( 2018), en tenistas sudamericanos hombres (17.04 ± 1.05 años), la clasificación reportada fue mesomorfo balanceado (2.5-4.9-2.7) lo anterior muestra una tipología corporal que permite desarrollar golpes y desplazamientos propios del tenis, es decir, de alta velocidad y potencia (Pardos-Mainer et al, 2017).…”
Section: Discussionunclassified
“…En cuestión para las damas, el somatotipo, presentó una tipología Ectomorfo balanceada, lo que no coincide con lo reportado por Sánchez-Muñoz et al Mesoendomórfico; Lentini et al Mesoectomorfico; Pereira, Endoectomórfico; y Endomesomorfico en Torres Luque et al Lo anterior, parece ser relevante ya que indicaría que las jóvenes chilenas evaluadas, presentan características corporales que afectan su rendimiento deportivo, en especial, el desarrollo de golpes y movimientos veloces y potentes, necesarios para el éxito en esta modalidad deportiva (Pardos-Mainer et al, 2017).…”
Section: Discussionunclassified